Unified design method of the cavity for injection molded spur gears - Lee, Sung-chul; Huh, Yong-jeong; Kim, Choong-hyun; Kwon, Oh-kwan (Annual Technical Conference - ANTEC, Conference Proceedings, 1998)
For injection molded spur gears, two design methods for the compensation of shrinkage are widely used. One is the module correction method and the other is the pressure angle correction method. Both methods are based on the assumption that shrinkage occurs toward the center of a molded gear. In this paper, we deal with general shrinkage and propose a unified design method of the gear cavity that is derived from the measured shrinkage rates. The proposed method imposes no restrictions on the shrinkage direction and provides a cavity with all of the fundamental gear design parameters.